2022
DOI: 10.1371/journal.pone.0271514
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcript signatures predict atherosclerotic lesion burden prior to a 2-year high cholesterol, high fat diet challenge

Abstract: The purpose of this study was to identify molecular mechanisms by which the liver influences total lesion burden in a nonhuman primate model (NHP) of cardiovascular disease with acute and chronic feeding of a high cholesterol, high fat (HCHF) diet. Baboons (47 females, 64 males) were fed a HCHF diet for 2 years (y); liver biopsies were collected at baseline, 7 weeks (w) and 2y, and lesions were quantified in aortic arch, descending aorta, and common iliac at 2y. Unbiased weighted gene co-expression network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…It is note that the results of EIF2 downregulation is acquired by IPA with canonical pathways. Studies have shown that downregulation of EIF2 signaling promotes progression of atherosclerosis 33 that is consistent with our findings. As expected, the machine learning disease pathways show that MerTK gene deficiency is associated with occlusion artery disease, heart dysfunction and brain disorders.…”
Section: Discussionsupporting
confidence: 93%
“…It is note that the results of EIF2 downregulation is acquired by IPA with canonical pathways. Studies have shown that downregulation of EIF2 signaling promotes progression of atherosclerosis 33 that is consistent with our findings. As expected, the machine learning disease pathways show that MerTK gene deficiency is associated with occlusion artery disease, heart dysfunction and brain disorders.…”
Section: Discussionsupporting
confidence: 93%
“…NHPs are ideal translational models because they share strikingly similar genetic, physiological, and behavior traits with humans (Tarantal et al 2022). Our recent NHP studies aim to better understand human disease processes have focused on genetics, epigenetics, caloric restriction, maternal caloric restriction and offspring health, maternal obesity and offspring health, NASH, and steatosis (Zimmerman et al 2023, Puppala et al 2022. In humans, studies comparing diseased vs. healthy liver have shown decline in cellular and biological functions (Wang et al 2023, Campagnoli et al 2022.…”
Section: Introduction (4625 Words)mentioning
confidence: 99%